Quantitative LIBS analysis of vanadium in samples of hexagonal mesoporous silica catalysts - Pouzar, Miloslav; Kratochvíl, Tomás; Capek, Libor; Smoláková, Lucie; Cernohorský, Tomás; Krejcová, Anna; Hromádko, Ludek (Talanta, 2011)
The method for the analysis of vanadium in hexagonal mesoporous silica (V-HMS) catalysts using Laser Induced Breakdown Spectrometry (LIBS) was suggested. Commercially available LIBS spectrometer was calibrated with the aid of authentic V-HMS samples previously analyzed by ICP OES after microwave digestion. Deposition of the sample on the surface of adhesive tape was adopted as a sample preparation method. Strong matrix effect connected with the catalyst preparation technique (1st vanadium added in the process of HMS synthesis, 2nd already synthesised silica matrix was impregnated by vanadium) was observed. The concentration range of V in the set of nine calibration standards was 1.3-4.5% (w/w). Limit of detection was 0.13% (w/w) and it was calculated as a triple standard deviation from five replicated determinations of vanadium in the real sample with a very low vanadium concentration. Comparable results of LIBS and ED XRF were obtained if the same set of standards was used for calibration of both methods and vanadium was measured in the same type of real samples. LIBS calibration constructed using V-HMS-impregnated samples failed for measuring of V-HMS-synthesized samples. LIBS measurements seem to be strongly influenced with different chemical forms of vanadium in impregnated and synthesised samples. The combination of LIBS and ED XRF is able to provide new information about measured samples (in our case for example about procedure of catalyst preparation).
Keywords: oxid křemičitý; prášky, zásypy, pudry; Silicon Dioxide; Particle Size; Porosity; Catalysis; Time Factors; katalýza; Chemistry Techniques, Analytical; poréznost; mikroskopie elektronová rastrovací; časové faktory; velikost částic; Vanadium; vanad; Spectrophotometry; spektrofotometrie; Microscopy, Electron, Scanning; chemické techniky analytické; Powders